Evaluating the effectiveness of website branding for institutions of higher learning in the Klang Valley - Wee, Vincent Eng Kim *; Wee, Vivien Mui Eik * (Sunway University, 2014)
The intention of this study is to determine the perception of students in evaluating the effectiveness of website branding for institutions of higher learning (IHLs). In addition, it is also to measure the effectiveness of website branding and the important role it plays as a medium in branding for institutions of higher learning. Besides, it is also to determine how brand recall may influence students’ decision to enrol into a particular school. The findings of this research are, hopefully, intended to provide accurate and useful information so as to facilitate further research in similar fields of study. Permission was granted by the Directors of the IHLs to deliver and collect the questionnaires. Questionnaires were given to 600 students of 10 selected IHLs in the Klang Valley. The respondents involved were students enrolled in the social science, technology and arts and design courses as well as all the school administrators ranging from the Principals to the key personnel of the departments. The respondents were asked about their perception with regard to evaluating the effectiveness of website branding for institutions of higher learning so as to gain their true interpretation and understanding of website branding. Responses from the respondents have shown that, generally, branding through a website was more important as compared to the use of other traditional mass media. The website was another medium that could be important for branding of IHLs. Many student respondents agreed that the website was more effective in their search for information compared to the use of the traditional mass media. From the traditional mass media, one might find it difficult to obtain the required information since many IHLs seldom employ any publicity using the traditional mass media. Educational institutions that posted good websites that could provide clear and sufficient information to their potential students would then have a competitive advantage over those that did not. The findings have shown that strong brand recall could provide customers with an assurance of quality and a reduction of search time in the purchasing process. Besides that, the findings have also indicated that branding through a website was definitely more effective in influencing the students in making decisions to enrol in their courses compared to the use of traditional mass media strategies.